Social stratication and access to resources in the alluvial tract of Ajay River situated in Ketugram block, Burdwan (W.B.): Acase study - Paul, Koyel (National Geographical Journal of India, 2022)
Every plot of a region in India has its productivity. Access to land is by and large determined by the prevailing social structure. Most productive land is usually owned by the privileged class in the social hierarchy. The present study examines if this structural control on land accessibility continues in the present times despite changes to the Indian social structure. A rural area in the Ajay River basin in West Bengal is purposively selected for the purpose to empirically examine the relationship. A micro-level survey has been carried out for the ownership distribution of land unit, the productivity of land, the land use. Availability of resources, their qualitative distributions is quantied through composite scores to arrive at meaningful conclusions. The study nds that social structure continues to act as a powerful force in access to resources but it is independent of the quality of life of the inhabitants.